IMPROVING NINTH STUDENTS’ SPEAKING SKILLS THROUGH THE GALLERY WALK TECHNIQUE AT SMP NEGERI 6 DENPASAR - PANDE MADE AYU MAHA DEWI; ANAK AGUNG PUTU ARSANA (JETA (Journal of English Teaching and Applied Linguistic), 2025)
In this study, the researcher conducted classroom action research to investigate the improvement of students’ speaking skills through the implementation of Gallery Walk Technique. This study was carried out at XI-1 class of SMP Negeri 6 Denpasar. The total number of students in this class were 40, however just 27 students were participated because 13 students were officially excused (dispensation) during the data collection period. This study conducted due to the researcher found that students still faced challenges to developing their speaking skills due to limited opportunity to practice their speaking in class, fear of making mistakes, and lack of confidence. To address this issue, the researcher implemented the Gallery Walk technique. To collect the data, the researcher used a combination of speaking tests (pre-test and post-tests), observation checklists, and questionnaires. The speaking tests were used to assess students’ performance in terms of comprehension, fluency, organization, accuracy, and pronunciation. These instruments were used across two cycles of the Classroom Action Research to evaluate improvements in students’ speaking skills and students’ attitudes. The findings showed an improvement from post-test 1 to post-test 2. In the first cycle, 55.56% of students passed the KKM, and in the second cycle, it increased to 81%. This shows that the Gallery Walk technique helped improve students’ speaking skills. Moreover, the observation and questionnaire also showed that students had better self-confidence, were more willing to communicate, took more risks, and felt less anxious. This means that Gallery Walk is effective technique to help students improve their speaking skills by creating a more interactive and enjoyable learning environment where the students could interact with their classmates by rotating from one station to other stations.